INTEGRASI PENDIDIKAN ISLAM DENGAN KURIKULUM KEWARGANEGARAAN: PERSPEKTIF MANAJEMEN PONDOK PESANTREN - Ade Aspandi (STKIP Subang, 2024)
This study aims to explore the integration process between Islamic Education and the Citizenship Curriculum in the management of education at Islamic boarding schools (Pondok Pesantren). Amidst the challenges of social change and globalization, it is crucial for educational institutions to produce individuals who not only possess a deep understanding of religion but also awareness of their rights and responsibilities as citizens. Islamic boarding schools, with their distinctive characteristics that combine religious and general education, offer opportunities to develop a curriculum that integrates these two aspects. This research employs a qualitative approach with a case study in several Islamic boarding schools with diverse characteristics and backgrounds. Data were collected through in-depth interviews with school administrators, educators, and field observations. The findings reveal that although integration between religious and civic education has been initiated, its implementation still faces challenges, such as limitations in human resources and a curriculum that is not yet fully coordinated. The study also highlights the importance of strong managerial support, collaboration between the schools and various stakeholders, as well as adjustments in teaching methods to foster a comprehensive understanding of citizenship aligned with Islamic values. Based on these findings, the study recommends enhancing the capacity of school administrators, developing a more holistic curriculum, and providing continuous training for educators. Keywords: Islamic Education, Citizenship Curriculum, Islamic Boarding Schools, Educational Management, Curriculum Integration